Ecosystem uptake and transfer of Sellafield-derived radiocarbon (14C) part 2: The West of Scotland. (15th February 2017) - Tierney, Kieran M.; Muir, Graham K.P.; Cook, Gordon T.; MacKinnon, Gillian; Howe, John A.; Heymans, Johanna J.; Hughes, David J.; Xu, Sheng
Abstract: Ecosystem uptake and transfer of Sellafield-derived radiocarbon ( 14 C) were examined within the West of Scotland marine environment. The dissolved inorganic carbon component of seawater, enriched in 14 C, is transported to the West of Scotland where it is transferred through the marine food web. Benthic and pelagic biota with variable life-spans living in the North Channel and Clyde Sea show comparable 14 C activities. This suggests that mixing of 14 C within the Irish Sea results in a relatively constant northwards dispersal of activity. Benthic species in the Firth of Lorn have similar 14 C enrichments, demonstrating that Irish Sea residual water is the dominant source to this area. Measured 14 C activities in biota show some similarity to western Irish Sea activities, indicating that dispersion to the West of Scotland is significant with respect to the fate of Sellafield 14 C releases. Activities measured in commercially important species do not pose any significant radiological risk. Highlights: Radiocarbon ( 14 C) uptake and transfer examined for the West of Scotland marine ecosystem. Dissolved inorganic carbon (DIC) enriched in 14 C at sites remote from Sellafield. Enriched 14 C activities in biota as a result of trophic transfer through the food web. Transport of Irish Sea water enriched in 14 C key to West of Scotland enrichment. Similar activities relative to the western Irish Sea are observed.